Implementing an Audiovisual-Based Flipped Learning Model to Increase Interest in Learning Pencak Silat - Cindy Aulia Sari; Toto Subroto; Regi Dwi Septian (Journal of Physical Education Health and Sport, 2025)
Interest in learning among students is a crucial element for achieving success in physical education, especially in pencak silat material which requires active participation from students. However, in learning pencak silat at the secondary school level, problems are often found such as low student interest and involvement, which is caused by traditional teaching methods. This research aims to increase students’ interest in learning through the use of a flipped learning model with the support of audiovisual technology media in learning pencak silat. This study uses the Classroom Action Research (CAR) approach developed by Kemmis and McTaggart, which was carried out in two cycles with the pre-cycle stage as the initial condition. The subjects in this research consisted of 32 class XII students at State Senior High School 1 Pabuaran. Data regarding student interest in learning was collected through a questionnaire adapted from Budiono (2012) and has been tested for validity and reliability. Data processing was carried out in a quantitative descriptive manner using the overall percentage of success. The findings of this research show a significant increase in students’ interest in learning, which rose from 38% in pre-cycle to 72% in cycle I and increased again to 91% in cycle II. The innovation of this research lies in combining the flipped learning model with audiovisual media which is applied in a structured manner in pencak silat learning at the secondary school level. These results indicate that the application of flipped learning supported by audiovisual technology is very effective in increasing students’ interest in learning pencak silat.